A cultura de índio, seu menino, vem de longe aqui : formação histórica e territorialização dos Tremembé/CE - Lopes, Ronaldo Santiago (2014)
This dissertation is based on the ethnography of a strategic selection of three Tremembé ethnic situations, which are situated in the backlands of Acaraú and Itarema, municipalities located in Ceará State (Northeast Brazil). My main aims are the following. Firstly, I reconstitute the historical and social formation of three localities, called Lagoa dos Negros, Telhas, and Queimadas, related to a particular origin myth which refers to Almofala, an extinct colonial Aldeamento in the seashore, where the Tremembé indians and other native populations were converted and gathered under missionary administration. According to the origin myth, these three localities were set up after a strong drought which happened in 1888 (the so called three eights) when a group of Tremembé families moved to the countryside and established close to the Lagoa dos Negros and, later on, they were segmented into smaller groups which started to live in other areas and places not far from the former location. Notably, I develop an anthropological approach to understand the historical formation of these three localities. Secondly, I analyze some processes of territorialization, which were emerged from the 1980s and had important consequences to these indigenous families throughout the next two decades. This historical dimension is re-appropriated and ressignified in ethnic terms. A third point of my work is the analysis of the construction of territorialities and also the cultural and symbolic dimensions which are formulated by the Tremembé Indians who live in these localities. Therefore, I investigate some cultural traditions and rituals, such as the Torém dance, but I also examine their multiple semantics, which constitute a transversal direction throughout the history understood by the Tremembé of the different social situations I researched. To sum up, there is a process of cultural actualization, which is still going on and presents itself through the ludic sphere as well as their political and religions dimensions, which are usually associated to the ritual presentation of the Torém